A simple cost-effective modification improves the quality of immunocytochemical staining in cervical scrape samples characterized by presence of excess mucus - Pawar, Sagar (J Histotechnol, 2014)
Immunocytochemistry (ICC) is a very important tool in a diverse range of biomedical research as well as in diagnostic cytopathology. Smears prepared from cervical scrapes contain a large amount of overlying mucus that interferes with the standard immunocytochemical staining protocol. A modified ICC protocol is described, which involves pretreatment of these smears with 1 mg/ml solution of Ambroxol hydrochloride in methanol for 1 hour. Source of Ambroxol hydrochloride was a 30 mg Mucolite(™) tablet, at a cost of 1.70 rupees (∼3·5 US cents) per tablet. This mucolytic solution effectively clears the mucus, facilitating the accessibility of the antibody to the antigenic determinants. This pretreatment resulted in the increased percentage of positively stained cells as well as staining intensity, leading to improved overall ICC staining and score. This is a novel modification that can be cost-effectively applied in ICC staining protocols for cytology samples characterized by the presence of excess mucus.